Professionals against populism : the Peres government and democracy - Keren, Michael (Albany : State University of New York Press, 1995)
Annotation This book, based on Shimon Peres's private papers, tells the unusual story of the Peres government of 1984-1986 in Israel. It is the story of an unpopular politician, demonized by his political enemies, who operates under great time restraints to manage a pluralistic democracy losing ground to enchanted masses in public squares. Lacking support from his own national unity government, Peres reverted to his old-time alliance with Israel's technocrats in his combat against populism. Michael Keren analyzes the role of legal professionals, strategic experts, and economists in the three main events of the Peres era: the scandal over the killing of two Arab terrorists by the General Security Service; the efforts to renew the peace process in the Middle East after the Lebanon war; and the economic stabilization program of 1985. The analysis illumines Israel's hitherto unexplored technocratic stratum and its ongoing struggle over Israel's nature as an advanced industrial state. This stratum, the author contends, has,been the moving force behind the construction of the nuclear reactor in Dimona in the 1960s, the combat against populism in the 1980s, and the Israeli-Palestinian peace process of today.
Frontmatter -- CONTENTS -- ACKNOWLEDGMENTS -- Chapter 1 INTRODUCTION -- Chapter 2 KNOWLEDGE AND DEMOCRACY -- Chapter 3 LAW AND SECURITY -- Chapter 4 IN QUEST OF MODERATION -- Chapter 5 THE SOCIAL CONTRACT -- Chapter 6 CONCLUSION -- Appendices -- NOTES -- BIBLIOGRAPHY -- INDEX
Includes bibliographical references (pages 133-141) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Peres, Shimon, -- 1923-2016.; Peres, Shimon, -- 1923-2016; Israel -- Politics and government -- 20th century; Populism -- Israel; Democracy -- Israel; Technology and state -- Israel; Israël -- Politique et gouvernement -- 20e siècle.; Populisme -- Israël.; Politique scientifique et technique -- Israël.; HISTORY; Democracy; Politics and government; Populism; Technology and state; Israel; Regeringen; Democratie; 1900-1999